Psychometric properties of the Breast Cancer and Lymphedema Symptom Experience Index: The Chinese version. (February 2016) - Shi, Shuang; Lu, Qian; Fu, Mei R.; Ouyang, Qian; Liu, Chao; Lv, Jing; Wang, Yingxin
Abstract: Purpose: To translate the Breast Cancer and Lymphedema Symptom Experience Index (BCLE-SEI) into Chinese language and evaluate its psychometric properties among breast cancer survivors with and without lymphedema in China. Methods: The BCLE-SEI was translated from English to Chinese language using an integrative translation method. The Chinese version was then evaluated for its psychometric properties using a comparison-group and test-retest method. Purposive sampling was used to recruit 219 breast cancer survivors with and without lymphedema in Beijing, China. Cronbach's alpha and test-retest reliability were conducted to assess the reliability; discriminant validity, criterion-related validity and exploratory factor analysis were examined to assess the validity of the instrument. Results: No semantic modifications to items were needed in terms of comparability of language and similarity of interpretability. Feedback on the pretest of the Chinese version by 15 Chinese breast cancer patients resulted in one item modification. The Chinese version of the instrument demonstrated excellent reliability (Cronbach's alpha = 0.930–0.967) and test-retest reliability ( r  = 0.572–0.705, p  < 0.001, n  = 34). A significant difference was observed between the lymphedema group and non-lymphedema group ( z  = −7.127, p  < 0.001). The criterion-related validity was supported by negative correlation with the Short-Form Health Survey (physical component summary, r  = −0.612; mental component summary, r  = −0.540). Factor analysis for symptom occurrence revealed 5 factors, which explained 66.1% of the total sample variance; 5 factors were also identified in symptom distress, which explained 70.6% of the total sample variance. Conclusions: The Chinese BCLE-SEI is a reliable and valid instrument to evaluate breast cancer-related lymphedema symptom experience for Chinese breast cancer survivors.